2012
DOI: 10.1002/adma.201202343
|View full text |Cite
|
Sign up to set email alerts
|

Catechol‐Based Biomimetic Functional Materials

Abstract: Abstract.Catechols are found in nature taking part in a remarkably broad scope of biochemical processes and functions. Though not exclusively, such versatility may be traced back to several properties uniquely found together in the o -dihydroxyaryl chemical function; namely, its ability to establish reversible equilibria at moderate redox potentials and pHs and to irreversibly cross-link through complex oxidation mechanisms; its excellent chelating properties, greatly exemplifi ed by, but by no means exclusive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
419
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 668 publications
(433 citation statements)
references
References 632 publications
(757 reference statements)
3
419
0
3
Order By: Relevance
“…The strongest binding energy of 29  k B T is measured for the interaction between Dopa and a titania‐coated tip. This is not unexpected since it has been pointed out previously that bidentate H‐bonding and metal coordination leads to strong adhesion between catechols and metal‐oxide surfaces 3a, 5. While our approach only provides equilibrated interaction free energies, insight into the exact binding mechanism is not possible.…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…The strongest binding energy of 29  k B T is measured for the interaction between Dopa and a titania‐coated tip. This is not unexpected since it has been pointed out previously that bidentate H‐bonding and metal coordination leads to strong adhesion between catechols and metal‐oxide surfaces 3a, 5. While our approach only provides equilibrated interaction free energies, insight into the exact binding mechanism is not possible.…”
mentioning
confidence: 66%
“…Both surface forces apparatus (SFA)2b, 3 and single‐molecule force spectroscopy (SM‐AFM)4 experiments indicated that Dopa adheres well to metal‐oxide surfaces by bidentate H‐bonding and metal coordination 3a, 5. In particular, Lee et al 4a.…”
mentioning
confidence: 99%
“…Application of this switch is shown in Figure 1. Poly (7) in the polycationic state destroyed almost 99.9% of E. coli and dead bacteria remained on the surface (Figure 1a), and, after hydrolysis to poly (8) (Figure 1b), almost 98% of the dead bacteria were released (Figure 1c). Additionally, poly (8) showed non fouling properties for proteins and Poly (9) [49] Poly(8) pH 13, 1 h (copolymer with poly(EGMA)…”
Section: Structural Effect On Hydrolysismentioning
confidence: 99%
“…Polymers 2015, 7, Reversible switch allowing switch between polycationic coating with antibacterial character and subsequently after switch release of dead bacteria and forming nonfouling surface have particular interest in coating for surgical or medical tools and application.…”
Section: Reversible Switch From Polycationic To Polyzwitterionic Statementioning
confidence: 99%
See 1 more Smart Citation